Fed-Batch Production of Saccharomyces cerevisiae L-Asparaginase II by Recombinant Pichia pastoris MUTs Strain - Rodrigues, David; Pillaca-Pullo, Omar; Torres-Obreque, Karin; Flores-Santos, Juan; Sánchez-Moguel, Ignacio; Pimenta, Marcela V.; Basi, Tajindar; Converti, Attilio; Lopes, André M.; Monteiro, Gisele; Fonseca, Luís P.; Pessoa, Adalberto Jr. (Frontiers in Bioengineering and Biotechnology, 2019)
L-Asparaginase (ASNase) is used in the treatment of acute lymphoblastic leukemia, being produced and commercialized only from bacterial sources. Alternative Saccharomyces cerevisiae ASNase II coded by the ASP3 gene was biosynthesized by recombinant Pichia pastoris MUTs under the control of the AOX1 promoter, using different cultivation strategies. In particular, we applied multistage fed-batch cultivation divided in four distinct phases to produce ASNase II and determine the fermentation parameters, namely specific growth rate, biomass yield, and enzyme activity. Cultivation of recombinant P. pastoris under favorable conditions in a modified defined medium ensured a dry biomass concentration of 31 gdcw.L-1 during glycerol batch phase, corresponding to a biomass yield of 0.77 gdcw.gglycerol-1 and a specific growth rate of 0.21 h-1. After 12 h of glycerol feeding under limiting conditions, cell concentration achieved 65 gdcw.L-1 while ethanol concentration was very low. During the phase of methanol induction, biomass concentration achieved 91 gdcw.L-1, enzyme activity 3315 U.L-1, specific enzyme activity 37.1 U.gdcw-1, overall enzyme volumetric productivity 31 U.L-1.h-1, while the specific growth rate fell to 0.039 h-1. Our results showed that the best strategy employed for the ASNase II production was using glycerol fed-batch phase with pseudo exponential feeding plus induction with continuous methanol feeding.